Bringing Ideology in: Differing Oppositional Challenges to Hegemony in Singapore and Malaysia. Issue 3 (4th December 2015) - Abdullah, Walid Jumblatt
Abstract : This article explores the nature of the main opposition parties to the incumbent hegemonic regimes in Malaysia and Singapore. I argue that the differing characters of these opposition parties should be considered. In Singapore, where there is no ideological challenge to the ruling party, I contend that even if the opposition takes over it will be the end of a hegemonic party but not hegemony. In Malaysia, the opposite is true. This article contributes to the literature on transition theory in two ways: (1) it recognizes the diversity of authoritarian regimes and enhances analyses of various authoritarian regimes by focusing on one type – hegemonic parties; and (2) it brings ideology into the reckoning by focusing on the nature of the opposition parties most likely to take over.